Evaluation of intrafractional head motion for intracranial stereotactic radiosurgery with a thermoplastic frameless mask and ceiling-floor-mounted image guidance device. (January 2021) - Tsuruta, Yusuke; Nakata, Manabu; Nakamura, Mitsuhiro; Uto, Megumi; Takehana, Keiichi; Hirashima, Hideaki; Fujimoto, Takahiro; Mizowaki, Takashi
Highlights: We evaluated intrafractional head motion in patients who received intracranial SRS. The intentional head motion in translation was mostly suppressed within 1 mm. The intentional head motion in rotation was mostly suppressed within 1°. A sudden large deviation was observed with low frequency. X-ray verification and correction are required during treatment. Abstract: Purpose: To evaluate intrafractional head motion (IFM) in patients who underwent intracranial stereotactic radiosurgery with the ExacTrac X-ray system (ETX) and a frameless mask. Methods: A total of 143 patients who completed a pre-treatment examination for IFM were eligible for this study. The frameless mask type B R408 (Klarity Medical & Equipment Co., Ltd., Guangzhou, China), which covers the back of the head, and the entire face, was used for patient immobilization. After the initial 6D correction and first X-ray verification ( IFM 1 ), X-ray verification was performed every 3 min for a duration of 15 min. The IFMp (2 ≤ p ≤ 6) was calculated as the positional difference from IFM 1 . In addition, the inter-phase IFM ( IP-IFM ) and IFM m were calculated. The IP-IFM was defined as | IFMp − IFMp -1 |, and IFM m as the difference between the values after all patients were asked to move their heads intentionally with the frameless mask on. Results: Both translational IFMp and IP-IFM exceeded 1 mm for a single patient, whereas, for all patients, the translational IFM m values were kept to within 1 mm in all directions. The proportions of the rotational IFMp, IP-IFM, and IFM m values within 0.5° were greater than 94.4%, 98.6%, and 90.2% for all of the rotational axes, respectively. Conclusions: A frameless mask achieved highly accurate patient positioning in combination with ETX and a 6°-of-freedom robotic couch; however, a deviation over 1 mm and 0.5° was observed with low frequency. Therefore, X-ray verification and correction are required during treatment.